Study of selective removal of CoS and NiS during purification of MnSO₄ electrolyte - Dube, Vuyiswa (Department of Chemical Engineering, 2015)
This research project investigated the selective removal of Co²⁺ and Ni²⁺ from a Co-Ni-Mn system through sulphide precipitation. The Co²⁺ and Ni²⁺ ions have adverse effects on the purity of the manganese product, thus, have to be removed via precipitation in a purification step. The main objective of this research was to understand the influence of local supersaturation on the purification process. This was important for controlling such a process to achieve residual ion concentrations of 0.3 ppm and 1.0 ppm for Co²⁺ and Ni²⁺ ions respectively, with minimum loss of the Mn²⁺ ions.